2023
DOI: 10.21037/tro-22-17
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of dosimetry on hippocampal-avoidance whole-brain radiotherapy in a regional hospital

Abstract: Background: Hippocampal-avoidance whole-brain radiotherapy presents a significant technical challenge in terms of treatment planning in order to spare the hippocampus. To ensure dose homogeneity and precision, the Radiation Therapy Oncology Group (RTOG) 0933 recommends strict dose criteria. To balance the clinical workload with these time-consuming treatments is a challenge. Noncompliance adversely might affect clinical outcomes in cancer patients with brain metastasis. We intend to retrospectively evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Hippocampal contouring and HA-WBRT planning directives of 3 cases were guided by the RTOG 0933 criteria, [10] and the technique and clinical study are described in our previous study. [14,15] To investigate whether a deviation of underdose in the HA region led to perihippocampal failure, we assessed the parameters of dosimetry in the HA-WBRT planning of our cases (Table 1). We compared the brain dose of patients A to C and the underdose region around the HA region by maping the MRI scans of intracranial failure and previous planning CT scan of simulation and found that a deviation of the underdosed region within the perihippocampal failure was approximately 55% to 63%.…”
Section: Dosimetric Analysis Of Hippocampal Failurementioning
confidence: 99%
“…Hippocampal contouring and HA-WBRT planning directives of 3 cases were guided by the RTOG 0933 criteria, [10] and the technique and clinical study are described in our previous study. [14,15] To investigate whether a deviation of underdose in the HA region led to perihippocampal failure, we assessed the parameters of dosimetry in the HA-WBRT planning of our cases (Table 1). We compared the brain dose of patients A to C and the underdose region around the HA region by maping the MRI scans of intracranial failure and previous planning CT scan of simulation and found that a deviation of the underdosed region within the perihippocampal failure was approximately 55% to 63%.…”
Section: Dosimetric Analysis Of Hippocampal Failurementioning
confidence: 99%